Pengaruh Model Pembelajaran SFAE Berbasis Tri Kaya Parisudha Terhadap Hasil Belajar Matematika Siswa - Widiasih, Luh Sri; Suarjana, I Made; Renda, Ndara Tanggu (Jurnal Ilmiah Sekolah Dasar, 2019)
This study aims to determine the difference of the students’ mathematics achievementbetween the students who are taught with student facilitator and explaining (SFAE) learning model based on Tri Kaya Parisudhaand those are taught with conventional learning in third-grade students of Gugus IV Gerokgak, Bulelengregency in academic year 2017/2018. The design of this study was quasi experimentalwith posttest only control group design. The population of this study was all the third-grade students of Gugus IV, Gerokgak which were 186 students. The sample of this study was the third-grade students of SD Negeri 2 Gerokgak with 34 students as experimental group and the third-grade students of SD Negeri 3 Gerokgak with 40 students as control group. Data collection was obtained by using objective test method. The data were analyzed by using T-test. The result of this study wasthitung = 7,38 with the significant level 55 and dk = 72 with ttabel= 1.99 so thitung = 7,38>ttabel = 1,99. Based on the test criteria, then H0 was rejected and Ha was accepted. The average score of mathematics learning achievement in the experimental group was 14.71, while the average score for the control group was 11.2. Based on the results above, it can be concluded that there was a significant effect toward the students’ mathematics achievementbetween the students who are taught with Student Facilitator and Explaining (SFAE) learning model based on Tri Kaya Parisudha and those are taught with conventional learning in third grade students of Gugus IV Gerokgak, Bulelengregency in academic year 2017/2018.